Gambaran Praktik Dukungan Suami Untuk Istri Dalam Kunjungan Antenatal Care (Studi di Wilayah Kerja Puskesmas Purwodadi II Kabupaten Grobogan) - Adila, Hani Lutfiatari; Suyatno, Suyatno; Dharmawan, Yudhy (Jurnal Ilmiah Mahasiswa, 2020)
Title : Description of Husband Practices For Wife In Antenatal Care Visit (Study in Public Health Care of Purwodadi II, Grobogan District)Background: Antenatal care is an effort made to reduce the number of maternal mortality. The husband as a partner and companion of pregnant women has an important role to support the pregnancy of their wives, including in the ANC visit. The support given by the husband can encourage pregnant women in enhancing the access to ANC services. Methods: A cross sectional study was conducted to describe husband's support for their wives in ANC visit in the work area of Purwodadi II Public Health Center, Grobogan Regency. The population in this study were all husbands whose wife's gestational age was in the third trimester in July 2019 and residing in the work area of Purwodadi II Health Center with a total of 140 people. 57 husbands were recruited using the simple random sampling technique. Data were collected through interviews based on the questionnaire then wereOanalyzed by using descriptive analysis. Result: The result of this study shows that most husbands provide good support for their wives in ANC visit.Â